TELAAH TERHADAP PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM (ONSLAAG VAN RECHT VERVOLGING) PADA PERKARA TINDAK PIDANA KORUPSI - Ihsan, Reza Noor (Belom Bahadat, 2022)
Decisions in corruption cases consist of sentencing decisions, acquittal decisions (vrijspraak) and decision is free from all lawsuits (onslaag van recht vervolging). This study aims to determine the implementation and juridicial implications of the decision is free from all lawsuits (onslaag van recht vervolging) in case of corruption. The normative research method used in reviewing decisions free from all lawsuits (onslaag van recht vervolging) in cases criminal acts of corruption. The results of this study on the implementation of the decision is free from all lawsuits (onslaag van recht vervolging) in cases of criminal acts of corruption is a necessity as long as the act is administrative in nature and does not enter the realm of criminal law so that it is not criminal responsibility but administrative responsibility with juridical implications the defendant is released from all lawsuits (onslaag van recht vervolging) in cases of corruption.